Young Adults' Perceived Purposes of Emerging Adulthood: Implications for Cohabitation. Issue 4 (18th May 2016) - Rogers, Adam A.; Willoughby, Brian J.; Nelson, Larry J.
ABSTRACT: The authors investigated associations between young adults' perceived purposes of emerging adulthood and their attitudes toward and participation in cohabitation. In a sample of 775 never married individuals, ages 18–29 (69% female, 69% white) from the United States, young people's perceptions of this period of life were associated with their acceptance of cohabitation, their reasoning for accepting cohabitation, and the likelihood of cohabiting. Results showed that the perception that emerging adulthood is a time to prepare for future family roles was negatively associated with acceptance of cohabitation whereas the perception that emerging adulthood is a time to take risks was positively associated with acceptance of cohabitation. The perception that emerging adulthood is a time to prepare for future family roles was associated with an increased likelihood of having cohabited while the perception that emerging adulthood is a time of possibilities was associated with a decreased likelihood of having cohabited. Implications for future research are discussed.